The Biotechnology of Lignocellulosic Waste Recycling Through Pleurotus spp. Cultivation - Akyüz, Mehmet; Kırbağ, Sevda (Springer, 2026)
The global agri-food industry produces significant quantities of lignocellulosic residues. It is therefore important to recycle these agro-wastes and investigate alternative uses, including their utilization in food production. Pleurotus species are renowned for their ability to decompose agricultural waste, and a number of studies have been conducted to investigate the use of different substrates for their cultivation. The biotechnological valorization of agro-residues through the cultivation of Pleurotus spp. constitutes a sustainable and eco-efficient strategy that enables lignocellulosic bioconversion, resource recovery, and the mitigation of associated environmental impacts. The competitiveness of these species in global production can be attributed to a number of factors, including their diversity of species and varieties, strong enzyme activities, favorable culture conditions, and nutritional and medicinal properties. Although Pleurotus species are cultivated worldwide on diverse substrates using different methods, this book chapter will summarize existing studies and provide general practical information on their production in five basic stages: (1) in vitro production of pure mycelia by tissue culture, (2) propagation of the main culture, (3) spawn production, (4) compost preparation and inoculation procedures, and (5) culture conditions. Presenting these methods in stages allows for the delivery of fundamental and practical information on the production of different Pleurotus species that yield high quantities in a relatively short period of time. This information is presented in a manner that emphasizes the importance of these unique and distinctive mushroom species and that offers fundamental guidance on how to produce them under culture conditions. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2026.
Keywords: Edible Mushroom; Mushroom Cultivation; Pleurotus Spp.; Recycling Of Lignocellulosic Waste